2016
DOI: 10.1519/jsc.0000000000001426
|View full text |Cite
|
Sign up to set email alerts
|

Player Selection Bias in National Football League Draftees

Abstract: Beyer, KS, Fukuda, DH, Redd, MJ, Stout, JR, and Hoffman, JR. Player selection bias in National Football League draftees. J Strength Cond Res 30(11): 2965-2971, 2016-Relative age effects (RAEs) have been studied as a potential factor associated with player selection bias in numerous sports. However, little research has examined the role of RAEs among National Football League (NFL) draftees. The purpose of the current study was to determine the existence of RAEs in NFL draftees from the last 10 NFL drafts. Draft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Countries use different cut-off dates which should also be examined for their role in RAEs. As previous studies have shown, scholastic quarters may present differently than calendar quarters in competition (4,18). Some other confounding factors could be considered in future studies, including age at time of competition and differences between competition years.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Countries use different cut-off dates which should also be examined for their role in RAEs. As previous studies have shown, scholastic quarters may present differently than calendar quarters in competition (4,18). Some other confounding factors could be considered in future studies, including age at time of competition and differences between competition years.…”
Section: Discussionmentioning
confidence: 92%
“…For instance, Hurley et al (18) found that in division I collegiate soccer, United States athletes had RAEs present when categorized by scholastic calendars. Beyer et al (4) found that RAEs were also present in National Football League draftees when assessed by scholastic quarters but not by calendar quarters. However, from this, RAEs were only present in skill positions and not in size positions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,18,20 In the National Football League (NFL), the impact of predraft injuries and surgical procedures, including anterior cruciate ligament reconstruction, rotator cuff tears, and shoulder labral tears, has been reported extensively from the medical records of the treating physicians; the findings portend unfavorable career prognoses for those with a musculoskeletal injury history, including a lower likelihood of a successful draft and a greater likelihood of decreased performance. 1,2,9,13,17…”
mentioning
confidence: 99%